Stability Analysis of Kunjukunju Rice Cultures - Jyothi R (Department of Plant Breeding and Genetics, College of Horticulture, 2002)
Stability analysis for Kunjukunju rice cultures in three locations of Palghat, Thrissur and Emakulam was conducted at Department of Plant Breeding and Genetics, College of Horticulture, Vellanikkara during 2001-2002. Among the eight Kunjukunju rice cultures studied the Kunjukunju rice culture K-6 was found to be stable in different environments for many of the yield and yield traits. It can be selected as the most stable, high yielding and well adapted Kunjukunju rice culture suitable for Pal ghat, Thrissur and Emakulam locations. The variety Kanchana showed to be specially adapted only to favourable environments for many of the yield traits and found to be unfavourable for many environments.